Shopping centre planning in Palmerston North : a suggested strategy : a paper presented in partial fulfilment of the requirements of Master of Arts in Geography at Massey University - Le Heron, Richard B (Massey University, 1968)
The rapid development of diversified multi-functional integrated shopping centres throughout the world has led one American observer to hail the "shopping environment" of such centres one of the new urban forms of the twentieth century. Palmerston North cannot even boast a large size planned shopping centre. It does, however, have a wide range of variously distributed centres, developed in accord with demand or as speculative ventures. This paper seeks to order and direction planning views on shopping centres in Palmerston North. A tentative strategy is consturcted and briefly applied to the Terrace End shopping centre complex. The author acknowledges the dual compilation and application of the Questionnaire for Retailers and Shoppers, with Mr B.R. Kells, a fellow geography masterate student at Massey University. The information collected and presented in the Shopping Centre Strategy could not have been obtained without the cooperation and time of shoppers and retailers in the shopping centres visited. Access to Valuation Department records is also gratefully acknowlewdged. [From Preface]
Maps best copy available. Original copy may be viewed in the library.
Keywords: Shopping centers; Palmerston North New Zealand; City planning